Pengaruh Kurs dan Produk Domestik Bruto Terhadap Neraca Transaksi Berjalan Melalui Pendekatan Error Correction Model (ECM) - Ina Namora Putri; Fuji Astuty (Jurnal Ekonomi Manajemen Perbankan, 2020)
Abstract The current account balance has increased compared to previous years, but the increase looks slow. So it is feared in global developments, especially those that could pose risks to the overall balance of payments. This study aims to provide empirical evidence about the factors affecting the current account which include the exchange rate and Gross Domestic Product. The current account balance is used to assess external economic stability in Indonesia. This research method uses a quantitative approach. And the data used are time series data from 1997 to 2017 using eviews 9. The model used is multiple linear regression model. The analysis was conducted in a short-term effect using Ordinary Least Square analysis techniques and Error Correction Mechanism. The results showed that the exchange rate had a positive and not significant effect, while the gross domestic product was significant.